2022
DOI: 10.1007/s42461-022-00664-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SLAM-Based Lidar Data Quality Metrics for Geotechnical Underground Monitoring

Abstract: Adverse ground behavior events, such as convergence and ground falls, pose critical risks to underground mine safety and productivity. Today, monitoring of such failures is primarily conducted using legacy techniques with low spatial and temporal resolution while exposing workers to hazardous environments. This study assesses the potential of novel simultaneous localization and mapping (SLAM)-based light detection and ranging (Lidar) data quality for rapid, digital, and eventually autonomous mine-wide undergro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The investigation described in [ 22 ] demonstrated a SLAM solution capable of accurately mapping underground mines at kilometer scales, using a spinning 2D-laser scanner and an industrial-grade inertial measurement unit mounted on a light vehicle. Finally, reference [ 23 ] analyzed the quality of SLAM-based mobile laser scanner (MLS) data for the accurate and efficient geotechnical monitoring of the underground mine environment. In addition, the applicability of real-time 3D SLAM based on normally distributed transform (NDT) and pose-graph optimization for complex underground space scenarios after disasters was examined in [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The investigation described in [ 22 ] demonstrated a SLAM solution capable of accurately mapping underground mines at kilometer scales, using a spinning 2D-laser scanner and an industrial-grade inertial measurement unit mounted on a light vehicle. Finally, reference [ 23 ] analyzed the quality of SLAM-based mobile laser scanner (MLS) data for the accurate and efficient geotechnical monitoring of the underground mine environment. In addition, the applicability of real-time 3D SLAM based on normally distributed transform (NDT) and pose-graph optimization for complex underground space scenarios after disasters was examined in [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This method used the structured data provided by rotating LiDARs. Authors of [29] generated results proved that LiDAR system is significantly more efficient for underground environment when compared to classical systems. The work presented in [30] involves an improvement of LeGO-LOAM by using SegMatch the results showed better accuracy in loopback detection.…”
Section: Cmes 2023 2 Related Workmentioning
confidence: 99%
“…Provide a 3D map representation. [27] Team of autonomous robots Provide a 3D map and SLAM [28] Rotating LiDAR Display 3D ego-motion [29] LiDAR and mobile laser Test mobile laser scanning [30] LiDAR Provide a 3D map and SLAM [31] LiDAR Geomechanically modelling for underground cavities [32] LiDAR Exploring the tunnel wall [33] LiDAR, inertial measurement unit, and encoders…”
Section: Workmentioning
confidence: 99%
“…As an alternative, lidar-based Simultaneous Localization and Mapping (SLAM) Mobile Laser Scanning Systems (MLS) can enable frequent, large-scale geotechnical monitoring due to significantly higher data acquisition efficiency than traditional inspections [15][16][17][18][19][20]. MLS can also offer safety benefits by removing operators from hazardous areas, as they can be integrated into autonomous robotic platforms such as quadruped robots or mining equipment [21]. Fahle et al [22] showed that multi-epoch MLS data could detect geotechnical hazards while achieving data quality with uncertainty on the millimeter-to-centimeter level.…”
Section: Introductionmentioning
confidence: 99%
“…MLS can also offer safety benefits by removing operators from hazardous areas, as they can be integrated into autonomous robotic platforms such as quadruped robots or mining equipment [21]. Fahle et al [22] showed that multi-epoch MLS data could detect geotechnical hazards while achieving data quality with uncertainty on the millimeter-to-centimeter level. MLS in underground mines has potential beyond geotechnical monitoring applications, including mapping and monitoring ground support performance [23], mine ventilation surveying [24], rock fragmentation analysis [25], and the control of autonomous vehicle applications [26].…”
Section: Introductionmentioning
confidence: 99%